Evaluation of potassium nutrition in productivity, quality and potassium use efficiency of garden pea in terrace soils (Bangladesh Journal of Agricultural Research, 2026)
Potassium (K) is key element for crop productivity and soil fertility. High demand of crop, K fertilization is ignored as appropriate amount in agriculture. Hence, an experiments was conducted in the research field of Horticulture Research Centre, BARI, Gazipur during Rabi season of 2017-18 and 2018-19 to find out the effective dose of potassium to improve growth, yield and quality of garden pea (Pisum sativum L.). Treatments were T1 = Control, T2 = K 30 kg ha-1, T3= K 40 kg ha-1, T4= K 50 kg ha-1 and T5= K 60 kg ha-1 following Randomized Complete Block Design with three replications. Application of 50 kg ha-1 K produced highest green pod (5352 kg ha-1) and seed yield (1568 kg ha-1), and increased 22.3 and 47.6% higher over K control. The highest amount of vitamin C (42.0 mg/100g) and protein (22.4%) were also noted under application of 50 kg ha-1 but. total K uptake (42.4 kg ha-1) was highest with 60 kg ha-1 K. The highest agronomic efficiency (10.1 kg kg-1), physiological efficiency of K (27.0 kg kg-1), and apparent K recovery efficiency (26.2%) were recorded of 50 kg ha-1 K. The maximum benefit cost ratio 5.67 for green pod and 2.91 for seed yields were registered with 50 kg ha-1 K and also superior based on growth, yield traits, nodulation, nutrient content in garden pea and soil fertility enhancement. Results suggest that application of K 50 kg ha-1 could support to achieve the maximum yield and quality of garden pea in experimental K deficient terrace soil.Bangladesh J. Agril. Res. 48(3): 307-323, September 2023